Towards an Ecosystem Approach to Management in Areas Beyond National Jurisdiction: REMPs for Deep Seabed Mining and the Proposed BBNJ Instrument - Christiansen, Sabine; Durussel, Carole; Guilhon, Maila; Singh, Pradeep; Unger, Sebastian (Frontiers in Marine Science, 2022)
The ocean plays a key role in sustaining life on our planet and is inextricably linked to biodiversity, climate, human well-being, and health. However, the governance of the ocean is primarily pursued through sectoral-based legal and institutional frameworks that falls short in ensuring the long-term protection of the marine environment and the sustainability of marine resources. This is especially concerning in areas beyond the limits of national jurisdiction (ABNJ) where human activities continue to expand. The existence of two distinct regimes in ABNJ, namely the High Seas (applicable to the water column, which is a global common) and the Area (applicable to the international seabed and its mineral resources, which are the common heritage of mankind), that have been largely regulated separately, impede the development and implementation of integrated marine environmental governance and biodiversity conservation in ABNJ. On the one hand, the International Seabed Authority (ISA), which is mandated to administer the mineral resources of the Area, is currently discussing a set of regulations to enable future exploitation activities. On the other hand, multilateral negotiations are taking place for the development of an internationally legally binding instrument for the conservation and sustainable use of marine biodiversity in areas beyond national jurisdiction (referred to as the proposed ‘BBNJ’ Instrument). Both processes offer a unique opportunity to foster an ecosystem approach to management (EAM) in ABNJ. In this article, we elaborate on options for stronger governance integration and the development of a coherent and collaborative interplay between these two processes. To this end, we explore the potential of Regional Environmental Management Plans (REMPs) established by the ISA as a case study to contribute to global biodiversity conservation, and the opportunity for the proposed BBNJ Instrument to promote overarching coherence to biodiversity conservation in ABNJ, premised on EAM. We conclude that the proposed BBNJ Instrument could have a pivotal role to streamline multilateral action for the conservation of biodiversity in ABNJ by adopting an ambitious, overarching environmental vision and strategic goals, accompanied by strong implementation and enforcement mechanisms.